Princípios ontológicos dos atos dos documentos aplicados à modelagem demo: uma investigação no contexto da ontologia corporativa - Katia Cardoso Coelho (2017)
Organizations are social entities that gather strategic, tactical and operational elements. These elements should coexist with the aim of producing goods and services. As complexity increases itis always a challenge to manage organizations, considering that the aforementioned elements can exist in different dimensions: technology, people, and processes, to mention but a few. To support managers in facing organizational complexities, a wide range of methods and techniques has been developed and employed. However, a good part of these methods is not able to produce models that effectively represent the organization. From such observation arose the Design &Engineering Methodology for Organizations (DEMO), a method initially created for purposes of Information Systems (IS) development. DEMO was later adapted to the purposes of modeling, re-design and re-engineering of organizations. Containing theoretical principles of theCorporative Ontology (CO), DEMO method emphasizes the construction of organizational models focusing on the communication patterns between humans. The method assumes that the communication between human actors constitutes the basis for a better understanding oforganizations. DEMO method, even though is a theoretically and methodologically wellgrounded resource, presents opportunities for new studies. One opportunity has connections both with the role that documents play within social interactions and how documents are linked with organizational processes. In this context, the present thesis discusses the role of documents in the scope of modeling practices. The main objective is to obtain improvements in practices of DEMO method throughout the construction of a specific artifact, namely, Documents Acts Model in DEMO. Our study aims to understand the documents nature as social objects, in a scope that goes beyond their mere informative or evidential roles. Here, we embraced the methodology ofDesign Science research (DSR) by means of which a set of seven guidelines were proposed.These guidelines favor the understanding, execution and evaluation of the artifact developed through the research. For the evaluation purposes, we made use of real documents of a healthcare institution, namely Hemominas Foundation, which served as the scenario for the models application